(untitled) (Journal of Chemical Engineering, 2013)
Mono Ethylene Glycol (MEG) is used primarily at low-temperature processing plant for extracting natural gas liquids. Typically a physical process plant comprises with gas dehydration system which allows for physical separation of water saturated gas by simple dew point depression and water condensation brought about by chilling from cross exchange with propane refrigerant. The resultant wet gas is prevented from freezing by injection of liquid desiccants to inhibit hydrate formation. The resulting dehydrated gas stream will have a dew point preciously equal to the saturated water volume of the gas at its coolest temperature. Mono Ethylene Glycol has been chosen as hydrate inhibitor because of its low volatility, low toxicity, low flammability, good thermodynamic behavior, and simple proven technology requirement and availability. But it has two common characteristic problems in regeneration plant that is fouling of equipment by iron carbonate, Ca+2/Mg+2 salt deposits and cross contamination of MEG and condensate contamination. MEG in condensate causes condensate specification problems, fouling of condensate stabilization equipment and contamination of wastewater streams. Condensate in MEG causes stripping effect due to condensate vaporization, lower operating temperature, higher MEG purities, and contamination of wastewater streams from MEG Regeneration system and burping of column due to condensate buildup. Another common problem is glycol losses due to carryover with dehydrated gas and which finally accumulates in pipelines and causes corrosion. Other reasons of glycol losses are higher column temperature, foaming, leaks at pump or pipe fittings, operated with excessive gas flow rates and rapid changes in gas flow rates. Column Flooding occurred if feed glycol circulation rate exceeded design limit and it does not allow proper separation of glycol and water separator and much glycol losses through vent line. This paper presents an experimental study of glycol losses. Effort has been made to investigate the causes and the study suggests some mitigation plans. Current study suggests the efficiency of the dehydration process depends on a large extent on the cleanliness of the glycol and the regular monitoring of glycol parameters such as glycol concentration, hydrocarbon content, salt content, solids content, pH stabilization, iron content, foaming tendency etc. Losses due to vaporization from reboiler can be minimized by adjusting operating parameters. By developing monitoring procedure and periodic maintenance about 90% operating problems of Glycol Regeneration Plant can be reduced. DOI: http://dx.doi.org/10.3329/jce.v27i1.15853 Journal of Chemical Engineering, IEB Vol. ChE. 27, No. 1, June 2012: 21-26